Charles D. Cooper papers - Cooper, Charles D. (Charles DeKay), 1769-1831.
Account book of medical services rendered and various other business, political, and personal accounts.
Physician and businessman, of Albany, N.Y.
Collection material in English.
Keywords: Business records -- New York (State) -- Albany; Medicine -- Practice -- New York (State) -- Albany; Albany (N.Y.) -- Politics and government; New York (State) -- Politics and government -- 1775-1865.; Businessmen; Physicians